Rain Water Harvesting in Kathmandu - Thanju, Jeewan P.; Shrestha, Basanta D. (Hydro Nepal: Journal of Water, Energy and Environment, 2011)
Not available. DOI: 10.3126/hn.v7i0.4230 Hydro Nepal Journal of Water, Energy and Environment Vol 7, July, 2010 Page: 17-19 Uploaded date: 31 January, 2011